Indonesia's Dilemma in Efforts to Disseminate The Covid-19 Vaccine (Rights and Obligations of the State for Citizens) and The Spread of Fake News That Disrupt Rule Enforcement - Pabbu, Amiruddin; Patawari, Patawari; Dewi, Mira Nila Kusuma (SASI, 2021)
The purpose of this study is to explain the effort of Indonesian government to fulfill its obligation towards its people’s right of health in this pandemic covid-19 situation that is by spreading the covid-19 vaccine on one side and people’s spreading fake information about covid-19 on the other side. The research method used is normative legal research. The result of this study shows besides the effort of Indonesian government to manage the pandemic situation, there are so many hoaxes about the pandemic that influence people to object the vaccine.  Therefore people are advised to really careful in receiving those information by sorting and choosing the correct information.